Production of sugar by hydrolysis of empty fruit bunches using palm oil mill effluent (POME) based cellulases: Optimization study - Zainan, Nur Hidayah; Alam, Md. Zahangir; Al-Khatib, Ma'an Fahmi Rashid (Academic Journals, 2011)
The utilization of lignocellulosic materials such as empty fruit bunches (EFB) from palm oil plant for bioethanol production attract increasing attention as an abundantly available and cheap renewable residue, especially in Malaysia where palm oil production is the major agricultural industry. The most challenging part in conversion of lignocellulosic materials to bioethanol is the hydrolysis process in order to obtain a reducing sugar. In this study, cellulase enzyme used for the hydrolysis was produced from palm oil mill effluent (POME), whose cost of production was considerably low as compared to commercial cellulases. The hydrolysis of EFB for sugar production as an initial step was statistically optimized based on agitation speed, EFB and cellulase concentrations using response surface methodology (RSM) through Box-Behnken design in 2 L bioreactor. The reducing sugar obtained is 16.85 g/L, which appeared at substrate concentration of 5.91%, enzyme concentration of 4.88% and agitation of 233 rpm.